The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.jproteome.5b00032
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Changes Associated with Atherosclerosis Progression for LDLR–/– Mice

Abstract: Atherosclerosis resulting from hyperlipidemia causes many serious cardiovascular diseases. To understand the systems changes associated with pathogenesis and progression of atherosclerosis, we comprehensively analyzed the dynamic metabonomic changes in multiple biological matrices of LDLR(-/-) mice using NMR and GC-FID/MS with gene expression, clinical chemistry, and histopathological data as well. We found that 12 week "Western-type" diet (WD) treatment caused obvious aortic lesions, macrophage infiltration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 70 publications
5
50
0
Order By: Relevance
“…The network pharmacology study showed that the LDLR target protein is associated with RSLD. Previous metabolomic studies have shown that LDLR protein deficiency causes a significant metabolic perturbation in TCA cycle, amino acid metabolism and fatty acid metabolism, and influences levels of taurine, linoleic acid, citric acid, leucine, and valine [33][34][35]. As shown in Figure 10, we observed similar changes in concentration of taurine, linoleic acid, citric acid, leucine, and valine in these related metabolic pathways.…”
Section: The Correlation Between Network Pharmacology and Metabolomicssupporting
confidence: 77%
“…The network pharmacology study showed that the LDLR target protein is associated with RSLD. Previous metabolomic studies have shown that LDLR protein deficiency causes a significant metabolic perturbation in TCA cycle, amino acid metabolism and fatty acid metabolism, and influences levels of taurine, linoleic acid, citric acid, leucine, and valine [33][34][35]. As shown in Figure 10, we observed similar changes in concentration of taurine, linoleic acid, citric acid, leucine, and valine in these related metabolic pathways.…”
Section: The Correlation Between Network Pharmacology and Metabolomicssupporting
confidence: 77%
“…Close to the completion of this manuscript, an interesting paper has been published demonstrating the link of atherosclerosis etiology with abnormal gut microbiota [206]. Studies with low-density lipoprotein receptor (LDLR) −/− mice, an atherosclerotic murine model, revealed that 12-week supplementation of high-fat diet could lead to evident aortic lesions, macrophage infiltration, and collagen level increase, concurrent with an up-regulation of inflammatory factors [206].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with low-density lipoprotein receptor (LDLR) −/− mice, an atherosclerotic murine model, revealed that 12-week supplementation of high-fat diet could lead to evident aortic lesions, macrophage infiltration, and collagen level increase, concurrent with an up-regulation of inflammatory factors [206]. This finding suggests that gut microbiota, combined with metabolisms of fatty acids and vitamin B 3 , could play a profound role in the onset and development of atherosclerosis [206] (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al, reported that a ‘western-type’ diet induced atherosclerosis progression in association with altered gut microbiota functions among others. Switching to a normal diet reversed this process implicating a crucial role of gut microbiota in atherosclerosis development 25 . In addition, it was reported that atherosclerosis susceptibility may be transmitted via transplantation of gut microbiota and that this may be influenced by intestinal microbial metabolism of certain dietary nutrients producing trimethylamine N-oxide 26* .…”
Section: Hfd-induced Dysbiosis and Disease Riskmentioning
confidence: 99%